Preservation of Mandailing Language Aspects, Mangambat, Through Integration of School Textbooks: a Feasibility Study - Hz, Benni Ichsanda Rahman; Pulungan , Anni Holila (EXCELLENCE: Journal of English and English Education, 2025)
This study aims to integrate the oral tradition of Mangambat into Indonesian and English language teaching materials in schools located in the Mandailing ethnic area, North Sumatra. Mangambat is a cultural tradition that functions as a ceremony to prevent the bride from being carried by the groom, using typical dialogue. This study uses a feasibility study design to evaluate the materials developed based on this tradition. The instrument used is a material feasibility checklist, which includes 15 assessment items related to the relevance, systematics, and impact of the material on learning. The trial was conducted on 16 10th grade high school students in Medan, and the results showed that the teaching materials involving Mangambat were well received by students, with a high average score on the quizzes tested. This study concludes that integrating oral traditions into the curriculum can enrich language learning while preserving local culture. The implication is that there needs to be further efforts in developing and implementing local wisdom-based teaching materials that can be used sustainably in formal education.